Building a Rabbani Generation: Integration of Knowledge and Morals in Islamic Education - Jimmy Malintang; Herson Anwar; Sumiarti Sumiarti; Wahyu Tri Wibowo; Izzatul Iffah (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2025)
Modern challenges demand Islamic education to instil knowledge and build strong moral character. This research aims to analyse the integration of science and morals in Islamic education as an effective model for building the Rabbani Generation. The research method used is qualitative with interviews, observation, and documentation techniques in Islamic educational institutions. The results of the study show that the success of this model is supported by several key factors, namely the role of educators as moral role models, the integration of curriculum based on Islamic values, extracurricular activities that develop students' character, and a social environment that is conducive to the formation of Islamic behavior. This study concludes that a holistic approach that emphasises the integration of science and morals can form intellectually intelligent individuals with noble character. The contribution of this research lies in the educational model that can be applied in various Islamic educational institutions as a solution to face the challenges of the modern era